Vibration analysis introduction - Primedia Workplace Learning ([United States] : PRIMEDIA Workplace Learning)
This interactive training unit is designed to familiarize trainees with the basic principles associated with measuring and analyzing vibration in rotating equipment. After completing this unit, trainees should be able to explain what vibration is and why it occurs in rotating equipment. They should also be able to describe how to measure vibration using a transducer, a vibration meter, and a vibration analyzer. Additionally, they should be able to explain how to analyze vibration using baseline data, vibration severity charts, and vibration signatures.
Keywords: Vibration